Elektromobilität 2035 - ein regionaler Blick: Effekte auf Wirtschaft und Erwerbstätigkeit durch die Elektrifizierung des Antriebsstrangs von Personenkraftwagen aus regionaler Perspektive - Anke Mönnig; Christian Schneemann; Enzo Weber; Gerd Zika; Robert Helmrich; Florian Bernardt (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Die Elektrifizierung des Antriebsstrangs bei Personenkraftwagen hat langfristig einen negativen Effekt auf das Wirtschaftswachstum und auf die Beschäftigung. Analysen bezüglich der regionalen Auswirkungen einer Elektrifizierung des Antriebsstrangs sind bislang jedoch nur wenig vorhanden und wenn, dann nur für spezifische Regionen. Mit der vorliegenden Analyse wurde versucht, diese Lücke zu schließen. Im Zentrum der Analyse steht die Annahme, dass bis 2035 Elektroautos einen Anteil von 23 Prozent an den Neuzulassungen und einen Bestand von 2,3 Millionen erreichen werden. Unter Zuhilfenahme der Szenarientechnik wurde eine Reihe von Annahmen getroffen und diese in das Analyseinstrument QINFORGE (Qualification and Occupation in the INterindustry FOrecasting Germany) integriert. Die Erweiterung QMORE (Quali-fication and Occupation in the INterindustry FOrecasting Germany Monitoring Regional) ermöglicht es, regionale Arbeitsmärkte mit ihrem Angebot und Bedarf sichtbar zu machen. [...] – – The electrification of the powertrain in passenger cars has a long-term negative effect on growth and employment at the federal level. However, analyses of the regional impacts of powertrain electrification are still scarce and only for specific regions. The present analysis attempts to close this gap. The central assumption of this analysis is that by 2035 electric cars will account for 23 percent of new registrations and have a stock of 2.3 million. The results show that the dynamics of regional labour markets vary significantly and that the regions are prepared for the structural change to a different extent. While some regions must expect job losses, there is also the potential to create many new jobs, as for example in the regions Düsseldorf/Ruhr or Frankfurt am Main. In particular, just more than 26 000 jobs will be lost in the regions of Munich and Stuttgart and 10 000 in the region of Hanover. Almost 55 percent of the 114 000 jobs that will be lost are located in these three regions. They are characterised by the large car manufacturers and the surrounding supply industry of vehicle construction. As a consequence of this almost all other regions are affected negatively directly and/or indirectly. Considering that the electro mobility scenario assumes an electric share of 23 percent by 2035 it can be assumed that a stronger market penetration will have significantly larger growth and employment effects. On the other hand, a positive growth and employment effect could be realised if Germany would achieve a position to supply the market with more domestically produced electric cars and with more domestically produced traction battery cells. The results shown above still do not include the impact of the current corona virus crisis. The further development depends on whether and how the corona pandemic affects the transformation process. So far, no car producer has been planning to reduce its investment activity in the area of electro mobility. From today's perspective, it therefore seems likely that only the pace of the transformation process will be affected. For example, a climate-friendly economic stimulus program could accelerate structural change.
Keywords: 330; Elektromobilität; Wirtschaftswachstum; Beschäftigungseffekt; Arbeitsmarkt; Regionaler Arbeitsmarkt; Regionalentwicklung; Szenariotechnik; Deutschland